Travelers With Chikungunya Virus Infection Returning to Northwest Italy From the Caribbean and Central America During June–November 2014. Issue 5 (17th June 2015) - Burdino, Elisa; Ruggiero, Tina; Milia, Maria Grazia; Proietti, Alex; Sergi, Giuseppina; Torta, Ilaria; Calleri, Guido; Caramello, Pietro; Tiberti, Donatella; Ghisetti, Valeria
Abstract Chikungunya virus (CHIKV) has recently emerged in the Caribbean. In Italy, CHIKV vector is documented in the Po river valley; therefore, a risk for autochthonous outbreaks is present. We report a case series of seven imported CHIKV infections in travelers returning from the Caribbean and Latin America occurring between June and November 2014, in the area of Turin, Northwest Italy, 3 years after the last imported cases were reported. These cases are a reminder of the need to always consider CHIKV infection in travelers from these epidemic areas as well as the importance of a prompt diagnosis.